2016
DOI: 10.1177/0886260516645816
|View full text |Cite
|
Sign up to set email alerts
|

To Stay or to Leave: Factors Influencing Victims’ Decisions to Stay or Leave a Domestic Violence Emergency Shelter

Abstract: Domestic violence (DV) emergency shelters play a vital role in supporting victims who seek to leave abusive partners and gain independence. Research indicates that numerous positive outcomes for victims and their children are associated with utilization of DV shelter programs. Yet, research also suggests that DV shelter programs may be unable to comprehensively meet the needs of all victims, and many choose to leave shelters soon after their arrival. To better understand the ways in which DV shelter programs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 27 publications
4
34
0
1
Order By: Relevance
“…Those survivors who do leave, especially those who go to a traditional secret-location DV shelter, may find that shelter-imposed separation from their usual sources of support triggers such profound loneliness that a return to an abusive relationship begins to seem more inviting, despite the attendant risk of further violence. Indeed, one study demonstrated that loneliness was a chief reason that survivors left shelters early and returned to their abusive partners (Fisher and Stylianou 2019 ). Another study cited loneliness as the primary reason survivors accepted apologies from their violent partners and returned to their relationships (Eisikovits and Band-Winterstein 2015 ).…”
Section: The Dangerous Consequences Of Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Those survivors who do leave, especially those who go to a traditional secret-location DV shelter, may find that shelter-imposed separation from their usual sources of support triggers such profound loneliness that a return to an abusive relationship begins to seem more inviting, despite the attendant risk of further violence. Indeed, one study demonstrated that loneliness was a chief reason that survivors left shelters early and returned to their abusive partners (Fisher and Stylianou 2019 ). Another study cited loneliness as the primary reason survivors accepted apologies from their violent partners and returned to their relationships (Eisikovits and Band-Winterstein 2015 ).…”
Section: The Dangerous Consequences Of Lonelinessmentioning
confidence: 99%
“…While many survivors credit shelters for increasing their safety (Sullivan and Virden 2017 ), a growing body of research indicates that the long-standing tradition of maintaining DV shelters at strictly secret locations, far from survivors’ home communities, and off-limits to visits from even their closest family and friends, make it enormously difficult, if not impossible, for survivors to maintain social connections (Fisher and Stylianou 2019 ; Kulkarni et al 2019 ). Many shelter residents experience a cessation of connection with virtually everyone and everything they have known, loved, and been part of (Thomas et al 2015 )—in other words, a perfect storm of loneliness.…”
Section: Responding To Survivor Loneliness During the Pandemic And Bementioning
confidence: 99%
“…Rules and agency environment influence survivors’ experiences and decisions to stay or leave on the micro, mezzo, and macro levels of experience. Fisher and Stylianou (2019) explored factors that underscore survivors’ decisions to stay in or leave shelter. Interviews with 33 women at four shelters illuminated three primary themes that guided whether participants stayed or left: (a) contextual environmental factors such as availability of housing and other resources; (b) relationship factors, including fear and safety needs; and (c) shelter specific factors, such as available support, but also rapport with staff and agency policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interviews with 33 women at four shelters illuminated three primary themes that guided whether participants stayed or left: (a) contextual environmental factors such as availability of housing and other resources; (b) relationship factors, including fear and safety needs; and (c) shelter specific factors, such as available support, but also rapport with staff and agency policy. Policies considered restrictive and unhelpful staff were major reasons for exit (Fisher & Stylianou, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation